To solve the system of equations using the substitution method, follow these steps:
We have:
- \( 9x - 3y = 12 \) (Equation 1)
- \( y + 6 = 2x \) (Equation 2)
Step 1: Solve one equation for one variable
Let's solve Equation 2 for \( y \): \[ y + 6 = 2x \] Subtract 6 from both sides: \[ y = 2x - 6 \]
Step 2: Substitute into the other equation
Now, substitute \( y = 2x - 6 \) into Equation 1: \[ 9x - 3(2x - 6) = 12 \]
Step 3: Simplify and solve for \( x \)
Distributing \(-3\): \[ 9x - 6x + 18 = 12 \] Combine like terms: \[ 3x + 18 = 12 \] Subtract 18 from both sides: \[ 3x = 12 - 18 \] \[ 3x = -6 \] Divide by 3: \[ x = -2 \]
Step 4: Substitute back to find \( y \)
Now substitute \( x = -2 \) back into the equation we derived for \( y \): \[ y = 2(-2) - 6 \] \[ y = -4 - 6 \] \[ y = -10 \]
Final Solution
The solution to the system of equations is: \[ (x, y) = (-2, -10) \]
You can check both equations to ensure that these values satisfy them.